2009
DOI: 10.1111/j.1471-4159.2009.06019.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain oxidative stress and selective behaviour of aluminium in specific areas of rat brain: potential effects in a 6‐OHDA‐induced model of Parkinson’s disease

Abstract: J. Neurochem. (2009) 109, 879–888. Abstract The ability of aluminium to affect the oxidant status of specific areas of the brain (cerebellum, ventral midbrain, cortex, hippocampus, striatum) was investigated in rats intraperitoneally treated with aluminium chloride (10 mg Al3+/kg/day) for 10 days. The potential of aluminium to act as an etiological factor in Parkinson’s disease (PD) was assessed by studying its ability to increase oxidative stress in ventral midbrain and striatum and the striatal dopaminergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…For this reason, the quantities of rare earth elements should be to the minimum necessary in magnesium alloys, especially cerium, which leads to more adverse effects than neodymium or lanthanum [111,116,117]. Although adverse effects of aluminum (possible contribution to Alzheimer and Parkinson disease) [121][122][123] and rare earth elements were reported in the literature, only few suitable investigations about the toxicological values (maximum quantities / no observed adverse effect level (NOAEL)) exists. Yuen et al [124] have mentioned that the annual aluminum exposure limit for a 60 kg adult is 35.88 mg year 1 (type of exposure limit: NOAEL).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the quantities of rare earth elements should be to the minimum necessary in magnesium alloys, especially cerium, which leads to more adverse effects than neodymium or lanthanum [111,116,117]. Although adverse effects of aluminum (possible contribution to Alzheimer and Parkinson disease) [121][122][123] and rare earth elements were reported in the literature, only few suitable investigations about the toxicological values (maximum quantities / no observed adverse effect level (NOAEL)) exists. Yuen et al [124] have mentioned that the annual aluminum exposure limit for a 60 kg adult is 35.88 mg year 1 (type of exposure limit: NOAEL).…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological, biochemical, and epidemiological studies suggest that Al contributes to the progression of several neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease [23,24]. It is also showed that the SLM function was significantly impaired and significant karyopyknosis of hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In our present study a dose dependent significant decrease in the activity of acetylcholinestrase was observed. Aluminium has been reported to enhance brain oxidative stress in rat brain (Sánchez-Iglesias et al, 2009). In some studies it has been reported to alter the function of blood brain barrier (Banks and Kastin, 1989) and has been controversially indicated as a factor in Alzheimer's disease (Ferreira et al, 2008).…”
Section: Discussionmentioning
confidence: 99%